The practice of everyday life - Certeau, Michel de 1925-1986 (Univ. of California Press, 1984)
Michel de Certeau considers the uses to which social representation and modes of social behavior are put by individuals and groups, describing the tactics available to the common man for reclaiming his own autonomy from the all-pervasive forces of commerce, politics, and culture. In exploring the public meaning of ingeniously defended private meanings, de Certeau draws on an immense theoretical literature in analytic philosophy, linguistics, sociology, semiology, and anthropology--to speak of an apposite use of imaginative literature.